Postoperative Pain Management and Perceived Patient Outcomes following Endoscopic Pituitary Surgery - Hoke, Austin T.K.; Malfitano, Madison; Zanation, Adam M.; Ebert, Charles S., Jr.; Senior, Brent A.; Kimple, Adam J.; Thorp, Brian D. (Journal of Neurological Surgery Part B: Skull Base, 2021)
Objectives Pain management remains a point of emphasis given the ongoing opioid crisis. There are no studies in the literature interrogating opioid prescribing and use following endoscopic pituitary surgery. This study investigates provider prescribing tendency, patient utilization of analgesics, and patient outcomes regarding pain management after endoscopic pituitary surgery.Methods We identified 100 patients undergoing endoscopic pituitary surgery at one institution from 2016 to 2018 in the electronic medical record (EMR) and state narcotic database to determine postoperative analgesic regimens. A telephone survey was used to characterize postoperative analgesic use and satisfaction with prescribed regimen.Results Fifty-two different pain control regimens were prescribed to the study patients. Also, 93% of study patients were prescribed an opioid postoperatively. The average quantity of opioids prescribed per patient in morphine milligram equivalents (MMEs) was 625 (equivalent 83 oxycodone 5-mg tablets) with an average MME/day of 59 (equivalent 8 oxycodone 5-mg tablets). A total of 71% survey respondents who used opioids reported using <25% of their prescription. The majority of prescription narcotic users consumed >50% of their postoperative opioid intake in the first 24 to 48 hours after discharge. There were no significant differences in pain outcome between opioid users and nonopioid users.Conclusion Vast heterogeneity exists in narcotic prescribing by providers at our institution following endoscopic pituitary surgery. Narcotic prescribing patterns exceeded most patients' analgesic needs. Opioid analgesics were not superior to nonopioids regimens in patient-reported pain outcomes in this study population.
Keywords: pain; opioids; pituitary; endoscopic; endonasal; analgesia; surgery; postoperative; prescription